2012
DOI: 10.1002/jbmr.1734
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral leptin regulates bone formation

Abstract: Substantial evidence does not support the prevailing view that leptin, acting through a hypothalamic relay, decreases bone accrual by inhibiting bone formation. To clarify the mechanisms underlying regulation of bone architecture by leptin, we evaluated bone growth and turnover in wild type (WT) mice, leptin receptor-deficient db/db mice, leptin-deficient ob/ob mice and ob/ob mice treated with leptin. We also performed hypothalamic leptin gene therapy to determine the effect of elevated hypothalamic leptin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
249
7
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(281 citation statements)
references
References 49 publications
21
249
7
4
Order By: Relevance
“…Furthermore, gender differences in leptin function in bone development have also been suggested with higher leptin receptor expression in female vs male rats . Moreover, subcutaneous leptin replacement in ob/ob mice resulted in increased trabecular bone area mainly in lumbar vertebra and to a lower extent in femur (Turner et al 2013), which agrees with the bone phenotype of female Scarb1-null mice in which hyperleptinemia is associated with enhanced bone formation in vertebrae and cortical bone; however, work remains to be done to understand why leptinemia is affected in females only.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, gender differences in leptin function in bone development have also been suggested with higher leptin receptor expression in female vs male rats . Moreover, subcutaneous leptin replacement in ob/ob mice resulted in increased trabecular bone area mainly in lumbar vertebra and to a lower extent in femur (Turner et al 2013), which agrees with the bone phenotype of female Scarb1-null mice in which hyperleptinemia is associated with enhanced bone formation in vertebrae and cortical bone; however, work remains to be done to understand why leptinemia is affected in females only.…”
Section: Discussionsupporting
confidence: 75%
“…As SR-BI was shown to be abundantly expressed in fat tissue (Acton et al 1994), plasma levels of leptin and adiponectine were measured in null mice. Leptin is recognized as an important bone growth modulator (Fleet 2000, Turner et al 2013. Null females showed high plasma levels of leptin under fasting conditions, as leptinemia was normal in Scarb1-null males, suggesting that leptin may explain the gender differences observed in bone status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…models with complete deficiency) or if they play an important homeostatic role in the regulation of peak bone acquisition and skeletal remodeling (3). Leptin acts primarily through peripheral pathways and increases osteoblast numbers and activity (4). Studies have shown that leptin levels are lower in preterm newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chemical lesions of neurons in the hypothalamus recapitulated the ob/ob phenotype and abrogated the effect of central leptin administration [22]. In contrast to the inhibitory effects of central leptin on bone formation, other studies have demonstrated an important role for peripheral leptin in stimulating bone formation [e.g., [23][24]. There are other signal systems that may also serve as neural output from the hypothalamus to bone tissues, including the neuropeptide Y and the cannabinoid receptors systems [25].…”
Section: Introductionmentioning
confidence: 99%